Business Accounting and Finance - Catherine Gowthorpe (United Kingdom Cengage, 2020)
Business Accounting and Finance, Fifth Edition, provides a clear, straightforward introduction to key management and financial accounting topics. In this new edition, a wealth of examples and real-life cases from well-known organizations, such as Lloyds, Tesco, Experian and Burberry, bring theory to life and prepare students for a successful career in the workplace.
Keywords: Business; Accounting; Finance; Business accounting; Textbooks; (ACC1057-N) Business Finance